Six mechanisms behind carer wellbeing effects: A qualitative study of healthcare delivery. (August 2019) - Al-Janabi, Hareth; McLoughlin, Carol; Oyebode, Jan; Efstathiou, Nikolaos; Calvert, Melanie
Abstract: Health and care services for patients may improve or harm the wellbeing of their family carers . Formal consideration of these effects (also known as spillovers) in decision-making is advocated, but, to date, little is known about how they occur. This paper presents the first empirical study to determine the mechanisms by which health and care services affect family carers' wellbeing. The study focused on three major health conditions: dementia, stroke, and mental health. Focus groups and interviews were conducted with 49 purposefully sampled care professionals and family carers in the UK between December 2016 and September 2017. Transcripts were coded and analysed thematically, using descriptive accounts and an explanatory account. The analysis generated six over-arching mechanisms by which health and care services affect family carers' wellbeing, through: (i) information (degree to which service delivery informs and trains family carers); (ii) management of care (shifts of responsibility for care between formal and family sectors); (iii) patient outcomes (services changing patient outcomes); (iv) alienation (feelings of alienation or inclusion created by service delivery); (v) compliance (barriers to patients complying and engaging with services); and (vi) timing or location (changes in the timing or location of services). Each mechanism was associated with sub-themes relating to both positive and negative spillovers on the family carers. The six mechanisms can be summarised with the mnemonic 'IMPACT'. The IMPACT mechanisms may be useful in designing and evaluating services to optimise the wellbeing of carers as well as patients. Highlights: Identified mechanisms linking patient services and carer wellbeing. Mechanisms were 'information', 'management', 'patient', 'alienation', 'compliance', 'timing'. Summarised by mnemonic IMPACT and relevant across conditions. Each mechanism generated positive and negative spillover.